Effect of non-genetic factors on wool quality traits in Patanwadi breed of sheep - A. R. Ahlawat; P. U. Gajbhiye; S. G.Gujjar; V.B. Dongre; A. C.Malasana (Journal of Livestock Biodiversity, 2025)
In all 2897 performance records were collected, compiled and analyzed to study the contribution of non-genetic factors affecting wool quality traits in Patanwadi sheep during a period of 13 years (1999-2011). Least squares analysis method (Harvey, 1990) was used to study the effects of location of herd, season and year of shearing and sex of the animal on wool quality traits. Wool quality traits studied included staple length, fibre diameter and medullation percentage. The overall means of staple length, fibre diameter and medullation percentage were 5.919 ± 0.122 cm, 41.055 ± 0.456 μ and 70.662 ± 1.197 %, respectively. Year and season of shearing as well as location of the herd had significant effects on all wool quality traits. The sex of the animal did not have a significant effect on wool quality traits. Performance of Patanwadi sheep can thus be improved by optimizing the environmental and managemental conditions.